2015
DOI: 10.1073/pnas.1414708112
|View full text |Cite
|
Sign up to set email alerts
|

Eluding catastrophic shifts

Abstract: Transitions between regimes with radically different properties are ubiquitous in nature. Such transitions can occur either smoothly or in an abrupt and catastrophic fashion. Important examples of the latter can be found in ecology, climate sciences, and economics, to name a few, where regime shifts have catastrophic consequences that are mostly irreversible (e.g., desertification, coral reef collapses, and market crashes). Predicting and preventing these abrupt transitions remains a challenging and important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 84 publications
(115 reference statements)
4
93
2
Order By: Relevance
“…The resulting Landau-Ginzburg theory, including fluctuations and spatial dependence is regarded as a meta-model of phase transitions and constitutes a firm ground on top of which the standard theory of phases of matter rests (9). Similar coarse-grained theories are nowadays used in interdisciplinary contexts -such as collective motion (52), population dynamics (53), and neuroscience (54)(55)(56)-where * This theory, developed three decades ago aims at explaining the seemingly ubiquitous presence of criticality in natural systems as the result of auto-organization to the critical point of a quiescent/active phase transition by means of diverse mechanisms, including the presence of two dynamical processes occurring at infinitely separated timescales (34,35). diverse collective phases stem out of the interactions among many elementary constituents.…”
Section: Significance Statementmentioning
confidence: 99%
“…The resulting Landau-Ginzburg theory, including fluctuations and spatial dependence is regarded as a meta-model of phase transitions and constitutes a firm ground on top of which the standard theory of phases of matter rests (9). Similar coarse-grained theories are nowadays used in interdisciplinary contexts -such as collective motion (52), population dynamics (53), and neuroscience (54)(55)(56)-where * This theory, developed three decades ago aims at explaining the seemingly ubiquitous presence of criticality in natural systems as the result of auto-organization to the critical point of a quiescent/active phase transition by means of diverse mechanisms, including the presence of two dynamical processes occurring at infinitely separated timescales (34,35). diverse collective phases stem out of the interactions among many elementary constituents.…”
Section: Significance Statementmentioning
confidence: 99%
“…The RD model studied in the paper could be generalized to higher dimensions, say, d = 2 and a stochastic component included in the model. A recent study [24] indicates that in a 2d system, discontinuous transitions are of the type shown in Fig. 1 could be replaced by continuous transitions under the conditions of limited diffusion, enhanced noise and quenched spatial heterogeneity.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, although the existence of alternate stable states is a key indicator of regime shifts, it may be challenging, in practice, to empirically identify these. Further, a recent paper showed that intrinsic stochasticity could dramatically alter the nature of the phase transitions (Villa Martín et al 2015), further exacerbating the challenge. The development and analysis of a land-use regime shift database, discussed earlier, would be a first step in identifying land-use regime shifts in practice.…”
Section: How Can Land-use Regimes Shifts Be Usefully Predicted?mentioning
confidence: 99%